1995
DOI: 10.1111/1523-1747.ep12324108
|View full text |Cite
|
Sign up to set email alerts
|

γ2 Chain of Laminin-5 Is Recognized By Monoclonal Antibody GB3

Abstract: Herlitz junctional epidermolysis bullosa is an autosomal recessive disorder characterized by generalized blistering at the lamina lucida of the cutaneous basement membrane. The monoclonal antibody GB3 has been used as a diagnostic probe because of its lack of reactivity in patient skin. The antigen recognized by GB3 has been identified as laminin-5, a glycoprotein consisting of three subunits (alpha 3, beta 3 and gamma 2). To identify the laminin-5 protein chain that contains the epitope recognized by GB3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 25 publications
2
36
0
Order By: Relevance
“…Later its 190 -200 kD ␣3 and 155 kD ␥2 chains are posttranslationally processed by proteolysis to 160 and 105 kD polypeptides, respectively. 49,50 BASEMENT MEMBRANE IN CARCINOMAS The role of the BM in carcinoma biology is not well understood. Based mostly on morphologic data, the loss of BM continuity has been associated with increasing malignancy.…”
Section: Laminin-5mentioning
confidence: 99%
See 1 more Smart Citation
“…Later its 190 -200 kD ␣3 and 155 kD ␥2 chains are posttranslationally processed by proteolysis to 160 and 105 kD polypeptides, respectively. 49,50 BASEMENT MEMBRANE IN CARCINOMAS The role of the BM in carcinoma biology is not well understood. Based mostly on morphologic data, the loss of BM continuity has been associated with increasing malignancy.…”
Section: Laminin-5mentioning
confidence: 99%
“…85 It has been suggested that the cleavage of laminin ␥2 chain by matrix metalloprotease-2 to 80 kDa fragment enhances breast epithelial cell motility. 81 The latter mechanism as a promotor in the invasion of colorectal carcinomas has been excluded by showing that there is no small cleaved polypeptides but only the normal 155,000 and 105,000 kD polypeptides 50 from the laminin ␥2 chain in carcinoma tissues. 61 Also, it has been recently suggested that the MT1-MMP plays a role in regulating the cell migration over laminin-5.…”
Section: Invasionmentioning
confidence: 99%
“…Immunofluorescence analysis using the mAb GB3, which binds to a conformational epitope in the laminin ␣3␤3␥2 heterotrimer (5,29), displayed a strong intracellular reactivity with the transfected LSV5 cells (Fig. 3).…”
Section: Delivery Of the Laminin ␥2 Chain Cdna Into Cultured H-jebmentioning
confidence: 99%
“…This polypeptide associated with the endogenous laminin ␣3 and ␤3 chains and formed a heterotrimeric ␣3␤3␥2 complex secreted extracellularly that was recognized by three distinct antibodies raised against each individual chain of laminin-5 and by mAb GB3. Because chain assembly into a complex preserving the native conformation of laminin-5 is required for binding with GB3 (5,29), GB3 recognition of the heterotrimer secreted by LSV5 cells in the culture medium and in the extracellular matrix suggests that the restored synthesis of ␥2 chain results in production of properly assembled laminin-5 molecules.…”
Section: Synthesis Of Endogenous Laminin-5 Reduces Cell Motilitykeratmentioning
confidence: 99%
“…This was a generous gift from Dr. Jonathan Jones (Department of Cellular and Molecular Structures, Northwestern University, Chicago, IL). The monoclonal antibody against type VII collagen raised from mouse, EBA2 [18] and monoclonal antibody to laminin 5, GB3 [7], were also used. Rabbit anti-mouse laminin antibody was purchased from Collaborative Biomedical Products/Becton Dickinson Labware (Bedford, MA).…”
mentioning
confidence: 99%